Anisotropic thermomagnetic effects on the universal stability of a diffusive state in porous media. Issue 8 (21st May 2021) - Saravanan, S.; Brindha, D.; Yamaguchi, H.
Abstract: A nonlinear study is made to find the influence of transverse anisotropy on the onset of thermomagnetic convection in a homogeneous and rotating porous medium. The medium is filled with a magnetic fluid and is subjected to centrifugal force with alternating directions. Unconditional nonlinear stability bounds are found by exploiting the variational principles. Effects of various parameters on the stability threshold are discussed. The overpredicting nature of the linear theory is demonstrated by isolating the subcritical region which cannot be obtained a priori. Abstract : A nonlinear study is made to find the influence of transverse anisotropy on the onset of thermomagnetic convection in a homogeneous and rotating porous medium. The medium is filled with a magnetic fluid and is subjected to centrifugal force with alternating directions. Unconditional nonlinear stability bounds are found by exploiting the variational principles. Effects of various parameters on the stability threshold are discussed. The overpredicting nature of the linear theory is demonstrated by isolating the subcritical region which cannot be obtained a priori.